2008
DOI: 10.1152/ajpheart.00970.2007
|View full text |Cite
|
Sign up to set email alerts
|

Blebbistatin inhibits the chemotaxis of vascular smooth muscle cells by disrupting the myosin II-actin interaction

Abstract: Blebbistatin is a myosin II-specific inhibitor. However, the mechanism and tissue specificity of the drug are not well understood. Blebbistatin blocked the chemotaxis of vascular smooth muscle cells (VSMCs) toward sphingosylphosphorylcholine (IC50 ϭ 26.1 Ϯ 0.2 and 27.5 Ϯ 0.5 M for GbaSM-4 and A7r5 cells, respectively) and platelet-derived growth factor BB (IC 50 ϭ 32.3 Ϯ 0.9 and 31.6 Ϯ 1.3 M for GbaSM-4 and A7r5 cells, respectively) at similar concentrations. Immunofluorescence and fluorescent resonance energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 54 publications
6
37
0
Order By: Relevance
“…MCP-1-stimulated macrophages showed an evident physical association between actin and myosin ( Figure 1b). Blebbistatin, a 1-phenyl-2-pyrrolidinone derivative (Figure 1a), at the concentration of 50 mM, drastically abrogated the co-precipitation of nonmuscle myosin heavy chain IIA with actin in all cells studied (Figure 1b), consistent with a previous work 33 showing that inhibition of NMII by blebbistatin induces actinomyosin complex disassembly.…”
Section: Blebbistatin Induces Actinomyosin Complex Disassembly In Immsupporting
confidence: 90%
“…MCP-1-stimulated macrophages showed an evident physical association between actin and myosin ( Figure 1b). Blebbistatin, a 1-phenyl-2-pyrrolidinone derivative (Figure 1a), at the concentration of 50 mM, drastically abrogated the co-precipitation of nonmuscle myosin heavy chain IIA with actin in all cells studied (Figure 1b), consistent with a previous work 33 showing that inhibition of NMII by blebbistatin induces actinomyosin complex disassembly.…”
Section: Blebbistatin Induces Actinomyosin Complex Disassembly In Immsupporting
confidence: 90%
“…Previous studies have shown that blebbistatin inhibits PDGF-BB-induced migration of SMC derived from the brain basilar artery of guinea pigs and an immortalized cell line of aortic smooth muscle cells obtained from Sprague-Dawley rat embryos (Wang et al, 2008). Effects of blebbistatin on SMC proliferation and migratory responses to injury are largely unknown; thus, additional studies exploring mechanisms of blebbistatin effects were performed with cultured RASMC.…”
Section: Blebbistatin and Neointimal Hyperplasia 119mentioning
confidence: 99%
“…Blebbistatin disrupts directed cellular motility and cytokinesis in vertebrate cells and inhibits contraction of contractile ring assembly (Straight et al, 2003). Exposure to blebbistatin has profound effects on SMC ex vivo, including disruption of actin-myosin interactions (Wang et al, 2008), inhibition of contraction of cultured SMC (Katayama et al, 2006), inhibition of ATPase activity of smooth muscle myosin (Eddinger et al, 2007), inhibition of KCl-induced tonic contractions produced by rabbit femoral and renal arteries (Eddinger et al, 2007), and inhibition of chemotaxis of SMC toward sphingosylphosphorylcholine and platelet-derived growth factor-BB (PDGF-BB) (Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of nuclear staining of MLCK in the A7r5 cell did not affect the significance of the results presented herein (data not shown). The quantification by FRET using this experimental protocol was described previously (31,32).…”
Section: Confocal/fret Microscopymentioning
confidence: 99%